Science news - Stołpiec, Katarzyna (No Limits, 2021)
A skin cancer imaging clip. Compounds for anti-cancer therapies. Faster diagnosis of Alzheimer disease. Membranes for removing trace amounts of heavy metal. Fungicides as saviors of the world's cultural heritage.